Rosiglitazone is Effective to Improve Renal Damage in Type-1-like Diabetic Rats - Huang, K-C.; Cherng, Y-G.; Chen, L-J.; Hsu, C-T.; Cheng, J-T. (Hormone and Metabolic Research, 2014)
A marked decrease of klotho expression was observed in the kidney of streptozotocin-induced diabetic rats (STZ rats) showing diabetic nephropathy. It has been documented that klotho is the target gene of PPARγ. However, the effect of PPARγ agonist on klotho expression in kidney of STZ rats remains obscure. Thus, we used rosiglitazone (TZD) as PPARγ agonist to investigate the effect on renal dysfunction in STZ rats. Treatment of TZD reversed the lower levels of PPARγ, klotho, and FGFR1 expressions in kidneys of STZ rats without the correction of hyperglycemia. Also, renal functions and structural defeats were improved by TZD treatment. Taken together, oral administration of TZD may improve STZ-induced diabetic nephropathy due to restoration of the expression of klotho axis through an increase in PPARγ expression without changing blood glucose in rats.
Keywords: diabetic nephropathy; TZD; PPARγ; FGFR; klotho; STZ rat